2016
DOI: 10.1016/j.jad.2016.02.065
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling vulnerabilities from outcomes: Distinctions between trait affect and depressive symptoms in adolescent and adult samples

Abstract: Background Trait negative affect and trait positive affect are affective vulnerabilities to depressive symptoms in adolescence and adulthood. While trait affect and the state affect characteristic of depressive symptoms are proposed to be theoretically distinct, no studies have established that these constructs are statistically distinct. Therefore, the purpose of the current study was to determine whether the trait affect (e.g. temperament dimensions) that predicts depressive symptoms and the state affect cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…It is plausible that current depression influences responses to other questionnaire measures to some degree, leading to exaggerated temperament scores during periods of depression. However, a recent study by Harding et al [68] investigated this issue and reported a clear statistical distinction between trait positive and negative affectivity, as measured by the EATQ-R, and depressive symptoms. They suggested that the EATQ-R ensured distinct construct measurement by separating items referencing depression, sadness, happiness, and pleasure as a distinct scale labelled Depressed Mood, which does not load onto the subscales used as measures of temperament in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that current depression influences responses to other questionnaire measures to some degree, leading to exaggerated temperament scores during periods of depression. However, a recent study by Harding et al [68] investigated this issue and reported a clear statistical distinction between trait positive and negative affectivity, as measured by the EATQ-R, and depressive symptoms. They suggested that the EATQ-R ensured distinct construct measurement by separating items referencing depression, sadness, happiness, and pleasure as a distinct scale labelled Depressed Mood, which does not load onto the subscales used as measures of temperament in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Further, identifying the potential role of trait negative affect in stress generation among relatively healthy samples of late adolescents may highlight a target for intervention. Given that negative affect is a prospective risk factor for depression and anxiety (Watson, Clark, & Carey, 1988), yet distinct from depression itself (Harding, Willey, Ashles, & Mezulis, 2016), identifying whether negative affect contributes to stress generation may elucidate a potential transdiagnostic mechanism contributing to mood and anxiety disorders. In particular, stress generation may be a process through which individuals with higher levels of trait negative affect are doubly at risk- both due to their tendency towards negative affective states and generation of negative interpersonal stressors.…”
Section: Negative and Positive Affect In Negative Interpersonal Eventsmentioning
confidence: 99%
“…Although negative and positive affects are closely related, positive affect is uniquely associated with psychopathology (Carl, Soskin Kerns, & Barlow, 2013; Gilbert, 2012; Harding et al, 2016). Individuals with low trait positive affect often experience less positive emotions and energy, which is characteristic of anhedonia- a hallmark of depression (e.g., Pizzagalli, 2013), and predicts greater depressive symptoms (Watson et al, 1988; Hudson, Harding, & Mezulis, 2015).…”
Section: Negative and Positive Affect In Negative Interpersonal Eventsmentioning
confidence: 99%